2018
DOI: 10.1038/s41598-018-28020-w
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 and O3 alter the feeding efficiency of Acyrthosiphon pisum and Aphis craccivora via changes in foliar secondary metabolites

Abstract: Elevated CO2 and O3 can affect aphid performance via altering plant nutrients, however, little is known about the role of plant secondary metabolites in this process, especially for aphids feeding behaviors. We determined the effects of elevated CO2 and O3 on the growth and phenolics of alfalfa (Medicago sativa) and feeding behaviors of the pea aphids (Acyrthosiphon pisum) and cowpea aphids (Aphis craccivora). Elevated CO2 improved plant growth, but could not completely offset the negative effects of elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…A previous study found that the application of genistein in an artificial diet prolonged the period of probing and shortened the passive ingestion duration of A. pisum , which suggested that genistein decreased the feeding efficiency of A. pisum [50]. Similar detrimental effects of genistein were also shown in other aphid species, i.e., Aphis glycines and Aphis craccivora [51,52]. Our result showed that the infestation of the Pisum host race induced the accumulation of genistein in M. sativa , which, in turn, reduced the survival rate of aphids and suggested that genistein is one of the components that are responsible for decreased fitness on M. sativa .…”
Section: Discussionmentioning
confidence: 75%
“…A previous study found that the application of genistein in an artificial diet prolonged the period of probing and shortened the passive ingestion duration of A. pisum , which suggested that genistein decreased the feeding efficiency of A. pisum [50]. Similar detrimental effects of genistein were also shown in other aphid species, i.e., Aphis glycines and Aphis craccivora [51,52]. Our result showed that the infestation of the Pisum host race induced the accumulation of genistein in M. sativa , which, in turn, reduced the survival rate of aphids and suggested that genistein is one of the components that are responsible for decreased fitness on M. sativa .…”
Section: Discussionmentioning
confidence: 75%
“…Likewise, the MED whitefly negatively affected by elevated O 3 levels, which is consistent with the increased developmental duration and decreased fecundity. Previous studies also showed that secondary metabolism can negatively affect the performance of piercing-sucking insects (Walling 2000, Yan et al 2018). For example, total phenolics and condensed tannins decreased whitefly population densities, growth rate, and delayed developmental time (Mansour et al 1997, Bialczyk et al 1999).…”
Section: Discussionmentioning
confidence: 92%
“…Secondary metabolites are also considered as part of plant defense mechanisms against biotic and abiotic stresses and variations in composition are phenotypic responses associated with resource availability and pathogen attack (Matros et al ., ). Additionally, these metabolites are known to alter feeding behavior of different herbivores (Yan et al ., ). The main phenolic found in the eggplant leaves was chlorogenic acid which is generally the predominant soluble phenolic compound in the leaves of this cultivar (Whitaker & Stommel, ).…”
Section: Discussionmentioning
confidence: 97%